What Career Guidance and Counseling Services Are Needed by Senior High School Students? - Darwin, Muhammad Riza; Farozin, Muh; Retnawati, Heri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
This study is a descriptive exploratory study. This study was conducted to analyze the guidance and counseling services in the career field that suits with the career needs of senior high school students. There were ten students of grade 12 in one of senior high school who participated in this study. Those students were chosen by using purposive sampling technique. The collection of data in this study was done by using interviews and need assessment instrument to investigate the needs of senior high school students in the field of career. The collected data then were analyzed with a descriptive method and exploratory. The research results show that senior high school students need the classical tutoring and individualized counseling services in the field of career counseling and counseling services, along with the subject of services that are required.